2017
DOI: 10.1038/srep42589
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of ABHD5 Lipolysis Activation

Abstract: Alpha-beta hydrolase domain-containing 5 (ABHD5), the defective gene in human Chanarin-Dorfman syndrome, is a highly conserved regulator of adipose triglyceride lipase (ATGL)-mediated lipolysis that plays important roles in metabolism, tumor progression, viral replication, and skin barrier formation. The structural determinants of ABHD5 lipolysis activation, however, are unknown. We performed comparative evolutionary analysis and structural modeling of ABHD5 and ABHD4, a functionally distinct paralog that dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 52 publications
3
58
0
Order By: Relevance
“…Several independent groups have likewise found that CGI-58 co-activates ATGL during catecholamine-stimulated lipolysis in adipocytes [2025]. Recently, the structural determinants of CGI-58-mediated ATGL co-activation in adipocytes have also been clarified [26,27]. Removal of N -terminal amino acids 10–31 of CGI-58 disrupts both CGI-58’s ability to localize to lipid droplets and its ability to co-activate ATGL [26].…”
Section: The Role Of Cgi-58 In Adipose Tissue Lipolysismentioning
confidence: 99%
See 3 more Smart Citations
“…Several independent groups have likewise found that CGI-58 co-activates ATGL during catecholamine-stimulated lipolysis in adipocytes [2025]. Recently, the structural determinants of CGI-58-mediated ATGL co-activation in adipocytes have also been clarified [26,27]. Removal of N -terminal amino acids 10–31 of CGI-58 disrupts both CGI-58’s ability to localize to lipid droplets and its ability to co-activate ATGL [26].…”
Section: The Role Of Cgi-58 In Adipose Tissue Lipolysismentioning
confidence: 99%
“…Within the N -terminus, three tryptophan residues (Trp21, Trp25, and Trp29) help form a tether for CGI-58 to stably interact with cytosolic lipid droplets [26]. Using a domain swapping approach from ABHD5 to a structurally similar variant of the α/β hydrolase domain-containing family ABHD4, Sanders and colleagues determined that two conserved amino acids (R299 and G328) were sufficient to confer ATGL co-activation onto ABHD4 [27]. In parallel, mutations of R299 and G328 residues in ABHD5 reduced adipocyte lipolysis without altering CGI-58’s interaction with perilipin [27].…”
Section: The Role Of Cgi-58 In Adipose Tissue Lipolysismentioning
confidence: 99%
See 2 more Smart Citations
“…The binding and activation of PNPLA2 by ABHD5 is negatively regulated by perilipin (PLIN) proteins (Fig. 2a), 15, 16, 19, 21 and inhibitors of ABHD5-PLIN interactions may thus serve as chemical probes and pharmacotherapies to promote fat lipolysis. 15 Recently, Sanders and colleagues 15 reported the discovery of two structurally distinct ligands for ABHD5—SR-4559, 4 and SR-4995, 5 (Fig.…”
Section: Resultsmentioning
confidence: 99%